A sphingolipid synthesis‐related protein OrmA in Aspergillus fumigatus is responsible for azole susceptibility and virulence. (14th August 2019) - Zhai, Pengfei; Song, Jinxing; Gao, Lu; Lu, Ling
Abstract: Previous studies identified that the budding yeast Saccharomyces cerevisiae have two sphingolipid synthesis‐related proteins, Orm1p and Orm2p, that negatively regulate the activities of SPT, which is a key rate‐limiting enzyme in sphingolipid synthesis. However, little is known about whether sphingolipids in the cell membrane, which are closely related to ergosterols, could affect the efficacy of azole drugs, which target to the ergosterol biosynthesis. In this study, through genome‐wide homologue search analysis, we found that the Aspergillus fumigatus genome only contains one Orm homologue, referred to as OrmA for which the protein expression could be induced by azole antifungals in a dose‐dependent manner. Deletion of ormA caused hypersensitivity to azoles, and adding the sphingolipid synthesis inhibitor myriocin rescued the azole susceptibility induced by lack of ormA . In contrast, overexpression of OrmA resulted in azole resistance, indicating that OrmA is a positive azole‐response regulator. Further mechanism analysis verified that OrmA is related to drug susceptibility by affecting endoplasmic reticulum stress responses in an unfolded protein response pathway‐HacA‐dependent manner. Lack of ormA led to an abnormal profile of sphingolipid ceramide components accompanied by hypersensitivity to low temperatures. Furthermore, deletion of OrmA significantly reduced virulence in an immunosuppressed mouse model. The findings in this study collectively suggest that the sphingolipid metabolism pathway in A. fumigatus plays a critical role in azole susceptibility and fungal virulence.